Encyclopaedia of women health and empowerment - 12 Wmone health, empowermentand economic development their contribution to national economy - Kumar, Meenal; Kumar, R.; Kumar, R. (New Delhi Deep & Deep Publications, 2009)
Women and socio-economic development